Curriculum implementation strategies in Informatics education at Madrasah Al Inayah - Kartika Diana (Himpunan Pengembang Kurikulum Indonesia, 2026)
The importance of madrasah readiness to meet the demands of 21st-century learning, particularly in equipping students with digital competencies aligned with Islamic values, is a consideration for school curriculum development. This study aims to explore the Informatics curriculum development strategy at the MA Swasta Al Inayah in Bandung City in the context of implementing the Kurikulum Merdeka. This study uses a qualitative case study approach, with grades 10 and 11 using the Kurikulum Merdeka, while grade 12 still uses the Kurikulum 2013. Data were collected through observations and in-depth interviews with teachers and the madrasah principal. The results show that curriculum development was carried out collaboratively and adaptively, utilizing the madrasah's internal strengths despite limited facilities and human resources. The integration of Islamic values into Informatics learning is one of the characteristics that strengthen the madrasah's identity. This study recommends further teacher training and increased ICT infrastructure support to sustain the implementation of the Kurikulum Merdeka, thereby improving the quality of learning in Islamic-based private madrasahs. Abstrak Pentingnya kesiapan madrasah dalam menghadapi tuntutan pembelajaran abad ke-21, khususnya dalam membekali murid dengan kompetensi digital yang selaras dengan nilai-nilai keislaman, menjadi hal yang perlu diperhatikan dalam pengembangan kurikulum di sekolah. Penelitian ini bertujuan untuk mengeksplorasi strategi pengembangan kurikulum Informatika di MA Swasta Al Inayah Kota Bandung dalam konteks penerapan Kurikulum Merdeka. Penelitian ini menggunakan pendekatan kualitatif dengan strategi studi kasus, di mana kelas X dan XI telah menggunakan Kurikulum Merdeka, sedangkan kelas XII masih menerapkan Kurikulum 2013. Data dikumpulkan melalui observasi dan wawancara mendalam dengan guru dan kepala madrasah. Hasil penelitian menunjukkan bahwa pengembangan kurikulum dilakukan secara kolaboratif dan adaptif, dengan memanfaatkan kekuatan internal madrasah meskipun terdapat keterbatasan fasilitas dan sumber daya manusia. Integrasi nilai-nilai keislaman dalam pembelajaran Informatika menjadi salah satu ciri khas yang memperkuat identitas madrasah. Penelitian ini merekomendasikan perlunya pelatihan lanjutan bagi guru serta peningkatan dukungan infrastruktur TIK untuk mendukung keberlanjutan implementasi Kurikulum Merdeka, sehingga dapat meningkatkan kualitas pembelajaran di madrasah swasta berbasis Islam. Kata Kunci: Informatika; Kurikulum Merdeka; madrasah; nilai keislaman